Carnivore coprolites from the lower Carnian (Upper Triassic) Chañares Formation, northwestern Argentina - Mancuso, Adriana Cecilia (2018)
With high organic content and abundant microbiota, feces are typically only preserved for a few days, weeks or months after deposition and mostly never enter the fossil record. The range of depositional conditions favorable for the preservation of feces is narrow, but depends on a large number of biotic and abiotic factors. Moreover, because the chemistry and microbiology of feces often promotes mineralization, discriminating between coprolites and some inorganic sedimentary structures is often difficult. We propose a protocol to identify coprolites in the fossil record that encompasses all the criteria previously defined. We then apply this protocol to identify putative coprolites from the lower Carnian (Upper Triassic) Chañares Formation of northwestern Argentina. Using a variety of analytical methods and several different criteria, we were able to identify them as carnivore coprolites. Based on extant analogs, the most probable producer would be a small carnivorous cynodont or archosauriforms, and the prey is likely a tiny therapsid or archosauriform. This is the first detailed report of carnivore coprolites from this unit, and provides direct evidence of trophic links in the Chañares ecosystem.